(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Cervical cancer in most cases does not occur on healthy mucous membranes, but against the background of precancerous conditions, such as grade 1, 2, 3 cervical dysplasia. They themselves are not malignant, but under certain conditions they are highly likely to provoke the development of oncological pathology. Precancer of varying severity is found in 30-50% of women aged 25-40 years; the growth of this pathology in women under 30 years of age is 2.2% per year. Precancerous lesions must be treated to reduce the risk of developing cancer.